Improving Communicative Competence and Speaking Skills in EFL/ESL Classrooms: Strategies, Techniques, and Pedagogical Approaches - Elmahdi, Omer Elsheikh Hago; AbdAlgane, Mohammed; Othman, Khalid; Alhaj, Mohamed Kamal Mustafa; Ibrahim, Intisar Zakariya Ahmed; Abdelrady, Abbas Hussein; Ahmed, Omaima Alkhier Mohamed (Forum for Linguistic Studies, 2025)
Communicative competence (CC) has proved to be the most pressing yet elusive objective in EFL/ESL learning. Learners often do not develop good speaking skills, with which they are dissatisfied, mainly due to inadequate opportunities for practice, high anxiety, and various institutional constraints. This study uses a qualitative design through document analysis and a systematic literature review of 35 peer-reviewed sources from different contexts in the Global South. The analysis covers the years 2018 to 2025 and thematically examines pedagogical strategies, technological tools, classroom practices, and cultural factors. Triangulation does enhance validity with critical attention to systemic barriers on the improvement of communicative competence and speaking skills in EFL/ESL classrooms. Findings also highlighted that the task-based language teaching (TBLT) approach significantly fosters fluency through engagement via real-world tasks, resisted by a teacher-dominant or exam-centric system. Automatic speech recognition (ASR) and technology tools substantially enhance pronunciation accuracy. However, they further accentuate inequity gaps in Asia and Africa due to inadequacies in enabling digital infrastructure. Listening attentively while shadowing boosts interactive communication; the method needs adaptation because of cultural norms like gender-segregated activities found in conservative societies. Major systemic barriers were found in the insufficient teacher training, rigid curricula, and misaligned assessment systems. Global and local approaches include the hybrid TBLT-grammar tasks and low-tech responses. They should be transformed into an institutional priority for teacher training, exam revision to test pragmatic skills, and more systematic partnerships with NGOs for the resource gap. Pedagogical innovation, cultural sensitivity, and equity-based policies that can encourage students to speak fluently in real-life communication.